TINJAUAN HUKUM TERHADAP PERBUATAN CURANG DALAM PILKADA - Mohamad Ikbal Kadir; Ostin Y Usman; Cahya Kamila Darise (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2026)
This study examines the legal perspective on fraudulent practices in regional head elections (Pilkada) in Indonesia, which continue to undermine democratic integrity. The problem addressed in this research is the persistence of electoral fraud such as money politics, abuse of power, and voter manipulation, despite the existence of legal regulations. The purpose of this study is to analyze the effectiveness of legal enforcement in addressing such violations and to identify the factors influencing its implementation. This research employs a normative legal method using statute and case approaches, supported by secondary data from legal documents, court decisions, and relevant literature. The findings indicate that although regulations governing electoral fraud are relatively comprehensive, their enforcement remains ineffective due to weak coordination among law enforcement agencies, limited evidence, and low public legal awareness. Additionally, socio-cultural factors contribute to the normalization of fraudulent practices in elections.